Does Research Centre in Zakah Institution Can be Considered as Zakah Workers or fī Sabilillah? - Aminudin Ma'ruf (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2022)
Many research centres have emerged in zakat institutions to encourage the efficiency of zakat fund management. It is a positive effort to optimize the use of zakat funds. This study aims to analyze the law on using zakat funds for research centres. To achieve this goal, this article compares the practice of IDEAS (Indonesia Development and Islamic Studies) research centre Dompet Dhuafa with the fiqh concept of eight groups of zakat recipients. This research will focus on defining the meaning of fī sabīlillah (for the cause of Allāh) and āmil (those employed for zakat) for eight groups of zakat expenditures by looking at the practice of Dompet Dhuafa in Indonesia. The results of this study indicate that research centres of zakat institutions can be considered 'amil if they have official permission from the government. However, research centres that do not have legal permits cannot be given zakat funds. This study will come with results from an Islamic perspective and suggestions for future research.   Abstrak: Dengan munculnya banyak pusat penelitian di lembaga zakat untuk mendorong efisiensi pengelolaan dana zakat, hal tersebut merupakan upaya positif untuk mengoptimalkan penggunaan dana zakat. Penelitian ini bertujuan untuk menganalisis hukum penggunaan dana zakat ke pusat penelitian. Untuk mencapai tujuan tersebut, artikel ini mencoba membandingkan praktik IDEAS (Indonesia Development and Islamic Studies) pusat penelitian Dompet Dhuafa dengan konsep fikih tentang delapan kelompok penerima zakat. Penelitian ini akan fokus pada pendefinisian makna fī sabīlillah dan āmil pada delapan kelompok penerima zakat dengan melihat praktik Dompet Dhuafa di Indonesia. Hasil penelitian ini mengindikasikan bahwa pusat penelitian lembaga zakat dapat dianggap sebagai pekerja zakat (‘amil) jika memiliki izin resmi dari pemerintah. Namun, pusat penelitian yang tidak memiliki izin hukum tidak dapat diberikan dana zakat. Studi ini akan datang dengan hasil dari perspektif Islam dan saran untuk penelitian masa depan.